(untitled) (Al-Qamar, 2025)
The concept of the soul is central in both Hinduism and Islam but is understood in fundamentally different ways. Hinduism upholds the doctrine of reincarnation (saṃsāra), where the soul undergoes repeated cycles of birth and rebirth, determined by one’s actions (karma). Liberation (moksha) is achieved only when the soul is purified and freed from this cycle, ultimately merging with the divine. This belief reflects a deeply philosophical approach to existence, morality, and destiny. Islam, however, categorically rejects reincarnation. The Qur’an and Hadith affirm that human life is a single and final test, followed by death, barzakh (the intermediate state), and resurrection on the Day of Judgment. The soul, created by God, continues after death and faces eternal reward or punishment in accordance with faith and deeds. Islam emphasizes human dignity, accountability, and the finality of death, presenting a linear view of life and the hereafter. This article critically reviews the Hindu concept of reincarnation and contrasts it with Islamic teachings, highlighting the profound differences in their approaches to life, death, and ultimate salvation.